EDUKASI DAN PELATIHAN PENGOLAHAN TEH DARI DAUN KARAMUNTING (RHODOMYRTUS TOMENTOSA) DI KELURAHAN LANDASAN ULIN UTARA - M. Andi Chandra; Wahyudin Bin Jamaludin (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2024)
The focus of community service activities is to give knowledge and information to the public about education and training on tea processing from karamunting (Rhodomyrtus Tomentosa) leaves. Activities in educational efforts related to the use of medicinal plants from Kalimantan resources and training on processing tea from karamunting leaves. This program was attended by 20 people. Extension methods in the form of lectures and direct demonstrations. Participants who participated in this activity focused only on the people who were members of the KWT (Kurnia Lestari). The media is used in the form of leaflets and brochures. Evaluation of the knowledge that has been given uses a pre-test and post-test system. Based on the pretest value, it can be seen that knowledge is 90%, while the post-test results show an increase in knowledge to (98%). The education and training program for processing tea from karamunting (Rhodomyrtus Tomentosa) leaves is considered effective as a preventive measure against the use of traditional medicine.  ---   Fokus dari kegiatan pengabmas yaitu memberikan pengetahuan kepada masyarakat mengenai edukasi dan pelatihan pengolahan teh dari daun karamunting (Rhodomyrtus Tomentosa). Kegiatan berupa edukasi tentang pemanfaatan tanaman berkhasiat obat sumber daya Kalimantan dan pelatihan pengolahan the dari daun karamunting. Program ini dihadiri 20 orang. Metode Penyuluhan berupa ceramah dan demonstrasi secarang langsung. Peserta yang berpartisipaso dalam kegiatan ini berfokus hanya pada masyarakat yang tergabung dalam KWT (kurnia lestari). Media yang digunakan berupa leaflet dan brosur. Evaluasi terhadap pengetahuan yang telah diberikan menggunakan sistem pre-test dan post test. Berdasarkan nilai pretest terlihat bahwa pengetahuan sebesar 90%, sedangkan hasil post-test menunjukkan adanya peningkatan pengetahuan menjadi (98%). Program edukasi dan pelatihan pengolahan teh dari daun karamunting (Rhodomyrtus Tomentosa) dinilai efektif sebagai tindakan preventif penggunaan obat tradisional.